2001
DOI: 10.1074/jbc.m101105200
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin-binding Region of Human Matrix Metalloproteinase-2

Abstract: Human matrix metalloproteinase-2 (MMP-2) contains an array of three fibronectin type II (FII) modules postulated to interact with gelatin (denatured collagen).Here, we verify that the NMR solution structure of the third FII repeat (COL-3) is similar to that of the second FII repeat (COL-2); characterize its ligand-binding properties; and derive dynamics properties and relative orientation in solution for the two domains of the COL-23 fragment, a construct comprising COL-2 and COL-3 in tandem, with each domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
25
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 52 publications
(51 reference statements)
6
25
0
Order By: Relevance
“…Additionally, the ligand binding surfaces of all three modules of MMP-2 have been mapped from 1 H and 15 N NMR perturbations induced by (PPG) 6 and the longer chain analog, (PPG) 12 , synthetic peptide mimics of gelatin (2-4). In line with the crystallographic evidence, which shows that the FN2 modules in MMP-2 point away from each other (5), our NMR studies of the interaction between Col domains and (PPG) 6 and (PPG) 12 have shown that consecutive Col modules contain distinct ligand-binding sites in which affinities for these ligands are virtually identical to those of the individual domains (3,4,8).Although the affinity of the MMP-2 Col domains for collagenous ligands appears by now to be well established, less is known regarding the specificity of the interaction. In our previous studies we found that the peptide PIIKFPGDVA, which corresponds to segment 33-42 of the pro-MMP-2, interacts with the three Col domains of MMP-2 in a manner that mimics the interaction with the collagen-like (PPG) 6 and (PPG) 12 peptides (3, 4).…”
supporting
confidence: 63%
See 4 more Smart Citations
“…Additionally, the ligand binding surfaces of all three modules of MMP-2 have been mapped from 1 H and 15 N NMR perturbations induced by (PPG) 6 and the longer chain analog, (PPG) 12 , synthetic peptide mimics of gelatin (2-4). In line with the crystallographic evidence, which shows that the FN2 modules in MMP-2 point away from each other (5), our NMR studies of the interaction between Col domains and (PPG) 6 and (PPG) 12 have shown that consecutive Col modules contain distinct ligand-binding sites in which affinities for these ligands are virtually identical to those of the individual domains (3,4,8).Although the affinity of the MMP-2 Col domains for collagenous ligands appears by now to be well established, less is known regarding the specificity of the interaction. In our previous studies we found that the peptide PIIKFPGDVA, which corresponds to segment 33-42 of the pro-MMP-2, interacts with the three Col domains of MMP-2 in a manner that mimics the interaction with the collagen-like (PPG) 6 and (PPG) 12 peptides (3, 4).…”
supporting
confidence: 63%
“…The latter may account for the competition between these peptides and gelatin for binding to FN2 domains. Interestingly, residues Gly-33 and Arg-34 are also involved in intramolecular interactions between the Col-3 module and the propeptide domain (3,5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations